2022
DOI: 10.3390/jcdd9080244
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Acute Kidney Injury in Patients Undergoing Redo Cardiac Surgery Using Cardiopulmonary Bypass

Abstract: Objective: This paper aimed to investigate the incidence and risk factors of postoperative acute kidney injury (AKI) in adult patients undergoing redo cardiac surgery with cardiopulmonary bypass (CPB), and explore the impact of AKI on early outcomes. Methods: A total of 116 patients undergoing redo cardiac surgery with CPB between November 2017 and May 2021 were included. Patients were divided into two groups, AKI group and non-AKI group, according to the Kidney Disease Improving Global Outcomes criteria. Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
1
0
2
Order By: Relevance
“…Cardiac surgery-associated acute kidney injury (CSA-AKI) occurs in nearly one-third of patients and represents one of the most important negative predictors of short-and long-term outcomes [26,27]. A recent authoritative article on patients referred for redo surgeries reported that AKI occurred in up to 54.3% of the cases, with renal replacement therapy required in 19.0% [28]. This compares favorably with data shown in our larger cohort.…”
Section: Discussionsupporting
confidence: 73%
“…Cardiac surgery-associated acute kidney injury (CSA-AKI) occurs in nearly one-third of patients and represents one of the most important negative predictors of short-and long-term outcomes [26,27]. A recent authoritative article on patients referred for redo surgeries reported that AKI occurred in up to 54.3% of the cases, with renal replacement therapy required in 19.0% [28]. This compares favorably with data shown in our larger cohort.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, a study conducted in China has reported that CPB time is independently linked to an increased risk of acute kidney injury following surgery for acute DeBakey Type I aortic dissection (43). Therefore, for high-risk patients undergoing AVR, reducing the ACC and CPB times may confer substantial advantages in using the Perceval valve, particularly for patients with pre-existing organ damage and infections or for those undergoing redo surgery (44,45). Two meta-analyses (30, 34) anchored on the comparison of the sutureless and rapid-deployment aortic valves in SURD-AVR had been published before our study was done.…”
Section: Discussionmentioning
confidence: 99%
“…Yaptığımız çalışmada da uzamış perfüzyon süresine sahip grubun hastanede kalış süresinin daha fazla olduğunu saptadık. Yapılan bazı çalışmalarda KPB süresinin akut böbrek hasarı için bağımsız bir risk faktörü olduğu belirtilmektedir (5,(13)(14)(15)(16). Xu ve ark.…”
Section: Bulgular Ve Tartişmaunclassified
“…( 16) yaptıkları çalışmada KPB eşliğinde yeniden/tekrar (revizyon) kalp cerrahisi yapılan hastalarda postoperatif akut böbrek hasarı için risk faktörlerini belirlemeye çalışmışlardır. Çalışmalarında; yüksek AST, ameliyattan önceki 2 hafta içinde yapılan koroner anjiyogram ve uzamış KPB süresinin, tekrar kalp cerrahisi geçiren hastalarda artmış postoperatif akut böbrek hasarı ile ilişkili olduğunu belirtmişlerdir (16). Yaptığımız çalışmada ise bu çalışmaların aksine perfüzyon süresi ile ABY arasında bir ilişki saptayamadık, bunun da cerrahi sırasındaki diğer ilişkili faktörlerden kaynaklanabileceğini düşünmekteyiz.…”
Section: Bulgular Ve Tartişmaunclassified